Creating interoperability within healthcare industry - Wu, Chen; Hadzic, Maja (IEEE, 2008)
During the last decade, a number of health initiatives have been undertaken in Australia. However, Australian medical systems still suffer from the chronic problem of inability to share information essential to the health and wellbeing of patients. The major causes for this are (1) the lack of a standardized format in which patient information is being kept, and (2) the lack of infrastructure to enable sharing of the information among different organizations and institutions. In this paper we propose the use of ontologies, to enable effective translation between different EHR formats, and use of web services to enable efficient information exchange and sharing. The proposed solution has the potential to greatly improve the way patient information is being used, and consequently reduce the associated costs in both human and financial terms.